A review of the state-of-the-art in solar-driven gasification processes with carbonaceous materials. (1st November 2017) - Loutzenhiser, Peter G.; Muroyama, Alexander P.
Highlights: Comprehensive review of current state of solar gasification processes. Sunlight is chemically stored and the feedstock upgraded via solar gasification. The resulting synthesis gas may be used in more efficient applications. Abstract: Gasification of carbonaceous feedstock with process heat derived from concentrated solar irradiation has been shown as a promising renewable pathway towards producing synthesis gas (mixtures of H2 /CO and some CO2 ). The carbonaceous feedstock is upgraded in calorific content equal to the enthalpy change of the endothermic reaction, which results in the net storage of solar energy in a chemical form. The process is carbon-neutral when biomass is used and the feedstock is transformed into a fuel with applications to more efficient processes ( e.g., Air-Brayton cycle), and the resulting syngas can be converted to liquid hydrocarbon fuels via know catalytic routes. A comprehensive summary is provided of the state-of-the-art in solar gasification, including thermodynamic and kinetic analyses and thermochemical reactor modeling, fabrication and testing for a range of carbonaceous feedstocks.